FIXED ASSETS OPTIMIZATION TO INCREASE RECURRING INCOME IN THE PROPERTY AND REAL ESTATE SECTOR - Ongkowijoyo, Meliana Kristin; Kohardinata, Cliff (Universitas Bunda Mulia, 2025)
Background: Business actors in the property and real estate industry experienced a decline in growth despite an improvement patterns of people's purchasing power in 2022.Purpose: The objective of this research is to empirically examine the impact of cash on hand, liabilities and fixed assets on recurring income.Research Method: This study employed a purposive sampling technique involving 24 property and real estate corporations listed on the Indonesia Stock Exchange from 2019 to 2022, resulting in a dataset of 96 observations. Panel data regression analysis was conducted using Stata 13 software. Findings: The study reveals that fixed assets significantly negatively impact recurring income, whereas cash on hand and liabilities exhibit no significant effects.Originality of Research: To the best of the researchers’ knowledge, no prior studies have specifically explored factors affecting recurring income in Indonesia’s property and real estate sector.